Teacher Competence and Motivation to Increase Skills in Using Educational Information Technology - Amahoru, Nurdiana; Jusriadi, Edi; Anggoro, Yusuf Alfian Renra (Manunggal Halim Jaya, 2024)
This research phenomenon is due to the low ability of teachers to utilize information technology in learning. The purpose of this research is to find out and analyze the influence of teacher competence on the use of information technology and to determine the influence of motivation teachers' work on the use of information technology in secondary education. Benefit study This It can be a reference source and contribute to the development of the field of human resource management, especially those related to educator competency and motivation and utilization of information technology. Then this research can provide input for secondary education in developing educational technology competencies and how to increase teacher motivation in improving their skills in using information technology. Type study This is study quantitative research approach used is explanatory research. Location study This is on UPT SPF Junior High School Negeri 6 Makassar. The population in this study were all teachers at UPT SPF SMP Negeri 6 Makassar, totaling 50 people. The method used in sampling is saturated sampling, or the entire population is used as a sample is as many as 50 people Because amount population is small everything is sampled. Data analysis used on study is quantitative with multiple Linear regression. The results of this research show that human resource competence has a positive and significant effect on the use of information technology. Teacher work motivation has a positive and significant effect on the use of information technology.